Conflict and Governance in the Establishment of Houses of Worship in Sungai Keledang Urban Village, Samarinda City: (A Document-Based Normative Juridical Study) - Iman Surya; Buhari Buhari (Institut Nalanda, 2026)
This study examines conflict and governance in the establishment of houses of worship in Sungai Keledang Urban Village, Samarinda City, using a document-based normative juridical approach. The analysis draws on demographic data, urban village monographs, the provisions of the Joint Regulation of the Minister of Religious Affairs and the Minister of Home Affairs Numbers 9 and 8 of 2006, local news reports, and documents related to institutional recommendations, community support, Building Approval, and mediation processes. The findings indicate that the conflict surrounding the establishment of the Toraja Church, El Shaddai Congregation, was not merely driven by religious differences, but was also shaped by issues of document verification, public communication, residents’ trust, and legal certainty in administrative procedures. Population density, the large number of neighbourhood units, and the uneven distribution of worship facilities further underscore the need for transparent, inclusive, and evidence-based governance. This study argues that conflict resolution should be pursued through document clarification, community deliberation, local government facilitation, and impartial mediation to ensure the protection of the right to worship while maintaining social harmony.